2010
DOI: 10.1080/17405620903113306
|View full text |Cite
|
Sign up to set email alerts
|

Coping with loneliness in childhood

Abstract: The aim of this study was to examine coping with loneliness during early, middle, and late childhood, which is a highly neglected research issue. Children's perceptions of coping with loneliness and coping with real loneliness experiences in the past were investigated. Interviews were conducted with 180 second, fourth, and sixth graders from Athens, Greece. Qualitative analyses of children's responses were done on the basis of a recent conceptualization of coping with stress in childhood and adolescence (Skinn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 38 publications
1
17
0
3
Order By: Relevance
“…Helpseeking as a form of coping appears to decline with age. The most frequent strategy that 7-12-year-old children reported they had used in the past to stop feeling lonely was seeking help from others, usually from parents, siblings, grand parents and peers [37]. However, as children become older they develop more capacity for self-regulation, have more autonomy, experience and knowledge and are able to use more coping strategies but surprisingly tend to use withdrawal as a coping mechanism for their loneliness [38].…”
Section: Age and Gendermentioning
confidence: 99%
“…Helpseeking as a form of coping appears to decline with age. The most frequent strategy that 7-12-year-old children reported they had used in the past to stop feeling lonely was seeking help from others, usually from parents, siblings, grand parents and peers [37]. However, as children become older they develop more capacity for self-regulation, have more autonomy, experience and knowledge and are able to use more coping strategies but surprisingly tend to use withdrawal as a coping mechanism for their loneliness [38].…”
Section: Age and Gendermentioning
confidence: 99%
“…Loneliness places individuals at risk of physical ailments, such as poor cardiovascular health and impaired immune responses [12]. Loneliness is also associated with mental health issues such as, psychosis, personality disorders, impaired cognitive functioning, low self-esteem and depression [2][3]. Particular concern is the correlation between loneliness and suicide or suicidal ideation.…”
Section: Introductionmentioning
confidence: 99%
“…That is, loneliness would negatively predict psychological well-being. The proposal is based on the burgeoning research [3,12], which demonstrate that loneliness is associated with poor psychological well-being. Because many awaiting-trial inmates are in social isolation, where the inmate have no social network and really do not have anyone or set of friends, the individual's psychological well-being of that individual would most likely be poor.…”
Section: Introductionmentioning
confidence: 99%
“…There is strong evidence that loneliness is related to anxiety [26][27][28] and depression [29][30][31], but few studies have reported associations between loneliness and somatic symptoms [1]. Loneliness among children and adolescents has been studied mainly in the school setting, and few researchers have tested initiatives to buffer feelings of loneliness [32][33][34]. Furthermore, as far as we are aware, no studies have reported on relational trust as a potential to reduce harmful effects of loneliness in school.…”
Section: Introductionmentioning
confidence: 99%